Caution with Journal Selection: Spam, Copycat Journals, and Predatory Publishing - Teixeira da Silva, Jaime A. (BioScientific Review, 2024)
The modern scholarly journal is currently faced with the challenge of upholding its principles in order to attract a continuous stream of authors to maintain its publishing status. Further, it also needs to be weary of unscrupulous players (including competitors) lurking in the global knowledge stream that pose an existential threat by diverting academics away from legitimate journals using underhanded or unfair practices, such as the use of spam or journals that employ copycat names. It is not always easy to distinguish predatory from exploitative journals, or underhanded from unfair practices, and even the use of or reliance on publishing blacklists does not offer potential authors a safe selection of journals to publish in. Authors and journals thus live in a volatile publishing environment in which they are confronted with constant threats. In biomedicine, these can translate into reputational damage to the journal and publisher if fake science or pseudoscience is published, since it puts at stake the journal’s reliability for biomedical information. For authors, particularly younger or less experienced ones whose careers depend on publishing advances, a mistake such as making a submission to a hijacked or copycat journal that impersonates the original journal may carry long-term negative reputational consequences. So, such a decision can be career altering.